Diagnosing PD‐MCI by MDS task force criteria: How many and which neuropsychological tests?. Issue 3 (1st December 2014) - Goldman, Jennifer G.; Holden, Samantha; Ouyang, Bichun; Bernard, Bryan; Goetz, Christopher G.; Stebbins, Glenn T.
Abstract Background The optimal properties of a comprehensive (level II) neuropsychological battery for determining Parkinson's disease mild cognitive impairment (PD‐MCI) by Movement Disorder Society (MDS) Task Force criteria remain unresolved. Methods Seventy‐six nondemented PD patients underwent PD‐MCI classification using a consensus diagnosis and level II criteria. We examined the optimal number of tests in each of the five designated cognitive domains, identified the best tests within each domain, and determined the best overall battery for PD‐MCI level II diagnosis. Results A battery with two tests per domain provided a highly practical, robust diagnostic assessment. Level II testing with the two best tests and impairment defined as 2 standard deviations below norms was highly sensitive and specific for PD‐MCI diagnosis. Conclusions Our findings strongly support the MDS Task Force Level II testing recommendations, provide a framework for creating an optimal, efficient neuropsychological test battery for PD‐MCI diagnosis, and offer specific test recommendations. © 2014 International Parkinson and Movement Disorder Society